What drives policy change for REDD+? A qualitative comparative analysis of the interplay between institutional and policy arena factors. (16th March 2019) - Korhonen-Kurki, Kaisa; Brockhaus, Maria; Sehring, Jenniver; Di Gregorio, Monica; Assembe-Mvondo, Samuel; Babon, Andrea; Bekele, Melaku; Benn, Vanessa; Gebara, Maria Fernanda; Kambire, Hermann W.; Kengoum, Felicien; Maharani, Cynthia; et al.
ABSTRACT: Reducing Emissions from Deforestation and forest Degradation (REDD+) has emerged as a promising climate change mitigation mechanism in developing countries. In order to identify the enabling conditions for achieving progress in the implementation of an effective, efficient and equitable REDD+, this paper examines national policy settings in a comparative analysis across 13 countries with a focus on both institutional context and the actual setting of the policy arena. The evaluation of REDD+ revealed that countries across Africa, Asia and Latin America are showing some progress, but some face backlashes in realizing the necessary transformational change to tackle deforestation and forest degradation. A Qualitative Comparative Analysis (QCA) undertaken as part of the research project showed two enabling institutional configurations facilitating progress: (1) the presence of already initiated policy change; and (2) scarcity of forest resources combined with an absence of any effective forestry framework and policies. When these were analysed alongside policy arena conditions, the paper finds that the presence of powerful transformational coalitions combined with strong ownership and leadership, and performance-based funding, can both work as a strong incentive for achieving REDD+ goals. Key policy insights The positive push of already existing policy change, or the negative stress of resource scarcity together with lack of effective policies, represents institutional conditions that can support REDD+ progress. Progress also requires the presence of powerful transformational coalitions and strong ownership and leadership. In the absence of these internal drivers, performance-based funding can work as a strong incentive. When comparing three assessments (2012, 2014, 2016) of REDD+ enabling conditions, some progress in establishing processes of change can be observed over time; however, the overall fluctuation in progress of most countries reveals the difficulty in changing the deforestation trajectory away from business as usual.